Financial Technology and Poverty Alleviation in Indonesia During the COVID-19 : Impact Evaluation Analysis - Ririn Nopiah; Retno Agustina Ekaputri; Armelly Armelly; Eka Dewi Anggraini (UNIVED Press, 2024)
The COVID-19 pandemic has brought significant changes, especially to each country's economic and financial sectors. Economic growth in Indonesia experienced a contraction entering mid-2021. This also impacted limiting economic activity, decreasing household consumption, unemployment risk, and increased poverty. In addition, there are changes in people's behavior, such as digital financing systems, non-cash payment systems, and online buying and selling transaction systems. Efforts to improve the economy are encouraged by stimulating people's economic productivity through adaptation to digital technology developments, especially using digital finance. However, the development of digital finance needs to be supported by public financial literacy and inclusion so that it can positively alleviate poverty. This study aims to analyze the impact of financial technology lending on poverty in Indonesia during the COVID-19 pandemic using instrumental variable analysis (IV) for 2019-202. The results of the study show that fintech lending has a negative effect on the poverty rate. However, it is not significant when other variables are added. E-commerce and the use of credit cards have a negative and significant impact on the poverty rate in Indonesia. In maximizing the role of Fintech in Indonesia, support and cooperation from the government, financial institutions, and various relevant stakeholders are needed.